As políticas públicas como instrumento de eficácia plena do direito fundamental ao lazer - Melo, Brielly Santana de (2015)
Fundamental social right of second dimension, leisure is born in order to require to the State an action not only for their protection but also for enforcement. Thus, it is seen that the Brazilian Federal Constitution of 1988 cites leisure at three different time, one of them in the Title II Rights and Fundamental Guarantees. Much was the doctrinal controversy as possible the effect of immediate applicability, prevailing currently the position that Article 5, §3º of the Basic Charter 1988 focuses on all of Title II, including the fundamental right to leisure. However, despite the immediate applicability guaranteed by the Federal Constitution, it was realized that leisure does not have the full effect, that is not able to generate all the effects necessary for their implementation and protection. This is because, although provided for in planning both at the constitutional level as infrastructure, leisure has only one aspect of such effectiveness, that is the legal. Therefore, it is missing the social effectiveness of leisure corresponding to their effectiveness, ability to produce effects in the social environment in order to reach the community and its traditions. It was also found that it is due to the lack of effectiveness the right to leisure is infringed and that the community is not able to define it or value it. Faced with this problem, we sought the solution by Georg Jelinek´s idea that leisure represents a positive fundamental right that require to the State an positive action. Therefore, based on the basilar super principle of democratic rule, the Dignity of the Human Person, and on the Principles of forbiddance to recession and of Social Progressivity, the implementation of Public Policies of State are mechanism of effective social fundamental right to leisure in order to raise awareness, implement and inform the community of the institute, and protect it from the offenses committed by individuals and even by the State. The work aims to discuss the implications brought to leisure due to its forecast in the legal system as a fundamental right , formulate a concept that embraces its interdisciplinarity, prove their importance to the dignity life of the individual and demonstrate public policies to be adopted the Legislative, Judiciary and Executive , and some subsidiary bodies of Justice, to ensure its effectiveness.